Epic arts in Renaissance France - Usher, Phillip John (Oxford Univ. Press, 2014)
Studies the relationship between epic literature and other art forms (painting, sculpture, architecture) in the French Renaissance, exploring the paradox that the heroes and themes in the art of the period are widely celebrated while the literary epics are largely unread
9780199687848
Keywords: Dolet; Etienne; Ronsard; Pierre de; Aubigné; Agrippa d'; Fata; Franciade; Tragiques; Art and literature; Epic literature; French; Literature in art